Sosialisasi Manfaat Saluran Pembuangan Air Limbah di Desa Bolihutuo Kabupaten Boalemo - Safrudin Tolinggi; Moh. Rivandi Dengo; Lisa Djafar (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The village of Bolihutuo has a population of 6,108. Based on the survey data from the Field Learning Experience I (PBL I) in hamlets one, two, and three, there are still residents of Bolihutuo village who do not have a wastewater disposal system. It can be seen that the distribution of ownership of wastewater disposal systems is based on the number in Bolihutuo village. The number of households (HH) without a wastewater disposal system is 184 (58.8%), and those with a wastewater disposal system outside the house are 2 HH (6%). The highest number of households without a wastewater disposal system is in hamlet 2, with 142 HH (64.4%) of the total HH in that hamlet. The purpose of this dedication is to provide an example of the construction and utilization of a good wastewater disposal system. The method used is a non-physical intervention in the form of socialization of the construction of a pilot wastewater disposal system to the community to increase the availability and use of wastewater disposal systems in every house in Bolihutuo village. The expected outcome of this activity is to raise awareness among the community about the importance of wastewater disposal systems for every household, especially in maintaining the quality of the environmental health ofÂ theÂ settlement